ChemInform Abstract: New Spiropyrans Based on 1, 3‐Benzoxazine‐2‐one: Acid Catalyzed Synthesis and Theoretical Insight into the Photochromic Activity. Issue 38 (September 2016) - Ozhogin, Ilya V.; Dorogan, Igor V.; Lukyanov, Boris S.; Mukhanov, Eugene L.; Tkachev, Valery V.; Chernyshev, Anatoly V.; Lukyanova, Maria B.; Aldoshin, Sergey M.; Minkin, Vladimir I.
Abstract: In situ generated protonated acetic acid catalyzes the reaction of methylene base (I) with salicylaldehydes to give new spiropyrans.